The Influence of CEO Characteristics on Financial Reporting Quality in Nigerian Non-Financial Listed Companies - MUSTAPHA, UMAR ALIYU; RASHID, NORFADZILAH; ABDULLAHI, SADIQ RABIU; OBASI, ROSEMARY OBIAGERI (The journal of contemporary issues in business and government, 2021)
There are several reasons through which financial statements are poorly prepared and reported in order to mislead the end-users. Also, the CEO’s claimed a high performance on their routine duties to achieve a targeted standard in their organisations. It may also be for them to maintain corporate goodwill in the eyes of the business community or to win the power of competitiveness, the craze to satisfy the greed of the company’s insiders. The objective of this study is to examine the influence of CEO characteristics on the financial reporting quality of the Nigerian non-financial listed companies. The population of the study is the all non-financial listed companies in Nigeria from the year 2012 to 2017, which saved as the sample of the study. The data was collected using secondary sources from the DataStream, annual reports and account of the selected companies. The analysis was carried out using multiple regression after the necessary post estimations tests for the panel data analysis. The study recognised a negative insignificant relationship between CEO tenure and financial reporting quality, while the CEO ownership provides a positive significant relationship with financial reporting quality using accrual earnings management. The study employed the use of agency and creative accounting theories to justified the proposed hypothesis. The findings of the study highlighted the current contributions of the CEO’s towed the credibility of the Nigerian corporation’s financial reporting practices.